Acid bone lysate activates TGFβ signalling in human oral fibroblasts - Strauss, Franz Josef (Sci Rep, 2018)
Demineralized bone matrix is a widely used allograft from which not only the inorganic mineral but also embedded growth factors are removed by hydrochloric acid (HCl). The cellular response to the growth factors released during the preparation of demineralized bone matrix, however, has not been studied. Here we investigated the in vitro impact of acid bone lysate (ABL) prepared from porcine cortical bone chips on oral fibroblasts. Proteomic analysis of ABL revealed a large spectrum of bone-derived proteins including TGF-β1. Whole genome microarrays and RT-PCR together with the pharmacologic blocking of TGF-β receptor type I kinase with SB431542 showed that ABL activates the TGF-β target genes interleukin 11, proteoglycan 4, and NADPH oxidase 4. Interleukin 11 expression was confirmed at the protein level by ELISA. Immunofluorescence and Western blot showed the nuclear localization of Smad2/3 and increased phosphorylation of Smad3 with ABL, respectively. This effect was independent of whether ABL was prepared from mandible, calvaria or tibia. These results demonstrate that TGF-β is a major growth factor that is removed upon the preparation of demineralized bone matrix.